How do board characteristics influence the ESG disclosure in Indonesia? - Sari, Tiyas Kurnia; Nadhira Fitriani (Jurnal Akuntansi dan Auditing Indonesia, 2023)
Our study investigates the influence of board characteristics on ESG disclosure for companies listed on the Indonesia Stock Exchange listed  from to 2018-2022. This study analyzes independent board members, board size, gender diversity, and audit committee independence as determinants of ESG disclosure in Indonesia’s public companies. The data were derived from Thompson Reuters and multiple linear regression was used to test the effects. The results showed that gender diversity was the only factor that was not significant. Independent commissionaires and board size positively affect ESG disclosure. Meanwhile, audit committee independence negatively and significantly affects ESG disclosure. Although ESG disclosure practices are still uncommon in Indonesia, the importance of board characteristics can be determined based on the results.